What Women Want (their men to do): Housework and satisfaction in Australian households - Gigi Foster; Leslie S. Stratton (Global Labor Organization (GLO), 2018)
The time allocated to household chores is substantial, with the burden falling disproportionately upon women. Further, social norms about how much housework men and women should contribute are likely to influence couples' housework allocation decisions and satisfaction. Using Australian data spanning the years 2001-2014, we employ a two-stage estimation procedure to examine how deviations from housework norms relate to couples' satisfaction. We find that satisfaction is negatively affected by predicted housework time, and that women's satisfaction, but not men's, is robustly affected by their partners' residual housework time. When he exceeds housework norms, she is happier with housework allocations, but less happy in broader dimensions. We suggest several reasons for our results, including that housework is more salient in women's lives than in men's, that housework in general is not a preferred activity, and that some degree of gender-norm conformity in regard to housework can positively affect women's life satisfaction.
Keywords: D13; I31; Z13; 330; Satisfaction; Social Norms; Housework